(untitled) (Research, Society and Development, 2022)
The demand for packaging made of biopolymers is currently increasing to meet the need for food conservation with lower environmental impact. The aim of this work was to develop and characterize polymer films spiked with bee pollen for use in food packaging. In this work, an experimental design of mixtures with fourteen tests was used, in which the independent variables (alginate, pectin and starch concentrations) were analyzed for the subjective aspects and the characteristics of moisture (ω), thickness (δ), water solubility (S) and water vapor permeability (WVP). Concentrations of 10g of pollen, 3ml of glycerol, and 30ml of 1m calcium chloride were established for all tests. Based on the best results for homogeneity, continuity, transparency, and flexibility, and the lowest values for ω, δ, S, and WVP, five tests were selected (G4, G6, G7, G8, and G10) that were characterized for their mechanical properties and optical microscopy. The results show that the G6 film (1/3g pectin + 2/3g starch) presented the best tensile strength (2.83MPa) but also the lowest elongation at break value (4.05%), showing itself to be more rigid, while the G8 film (2/3g alginate + 1/3g starch) achieved a better elongation (9.60%). Young’s modulus of elasticity ranged from 35.05 to 137.06MPa. In optical microscopy, the pollen grains were clearly observed in all optimized formulations. The properties observed in the optimized films are promising for use as edible and biodegradable packaging, but further testing is recommended.